Impact of Covid-19 on Organizational Prosperity: Management Challenges of SMES - Damian BANAT; Dominik BANAT (Communications of International Proceedings, 2021)
The main goal of the paper is to assess the COVID-19 impact on the organizational prosperity and the identification of management challenges of SMEs. A literature review was conducted by the Systematic Literature Review (SLR) method. This study indicates that the key success drivers for business growth during the pandemic are innovations and the implementation of emerging technology. It has been recognized that budgetary amendments are required in order to change the allocation of financial support to the IT functions of the organizations. The qualitative study results have shown that the main challenges of SMEs’ leaders are ensuring financial liquidity, protection of jobs, and inadequate digital capabilities of personnel and organizations. This is the first paper to propose the consideration of management challenges due to COVID-19 in terms of SMEs in Poland based on the ICT sector.
Keywords: COVID-19; business prosperity; leadership; SMEs